Incidence and Risk Factors of Nasal Carriage of Staphylococcus aureus in HIV-Infected Individuals in Comparison to HIV-Uninfected Individuals: A Case–Control Study. (March 2016) - Kotpal, Ruchi; S., Krishna Prakash; Bhalla, Preena; Dewan, Richa; Kaur, Ravinder
The study was conducted to evaluate the prevalence of nasal colonization of Staphylococcus aureus in individuals with HIV infection attending the Integrated Counselling and Testing Centre in a teaching hospital and compare the prevalence with HIV-uninfected individuals. A case–control study was conducted among newly diagnosed HIV-infected individuals and an equal number of age-group and sex-matched HIV-uninfected individuals, and nasal swabs were collected from both the samples. Sociodemographic and clinical data were collected through individual interviews. Ethical aspects were respected. A total of 100 individuals participated in the study, and 22 (44%) of the 50 HIV-infected cases were colonized by S aureus, including 19 (86.4%) methicillin-sensitive S aureus (MSSA) and 3 (13.6%) methicillin-resistant S aureus (MRSA). Only 12 (24%) strains were isolated from 50 HIV-uninfected individuals, with 11 being MSSA and 1 being MRSA. This difference in the isolation rate was statistically significant ( P = .035). The 2 most commonly encountered risk factors in both the groups appeared to be history of tuberculosis and history of surgical procedures but none being statistically significant ( P = .093 and P = .996). All the strains of S aureus were sensitive to mupirocin. The study concluded that HIV-infected individuals are at a higher risk of carriage as compared to HIV-uninfected individuals. By eliminating carriage in immunocompromised individuals, infections due to S aureus can also be minimized.